Comorbidities and predictors of health‐related quality of life in Dravet syndrome: A 10‐year, prospective follow‐up study. Issue 4 (22nd February 2023) - Makiello, Phoebe; Feng, Tony; Dunwoody, Benjamin; Steckler, Felix; Symonds, Joseph; Zuberi, Sameer M.; Dorris, Liam; Brunklaus, Andreas
Abstract: Objective: Dravet syndrome (DS) is a severe developmental and epileptic encephalopathy, leading to reduced health‐related quality of life (HRQOL). Prospective outcome data on HRQOL are sparse, and this study investigated long‐term predictors of HRQOL in DS. Methods: One hundred thirteen families of SCN1A ‐positive patients with DS, who were recruited as part of our 2010 study were contacted at 10‐year follow‐up, of which 68 (60%) responded. The mortality was 5.8%. Detailed clinical and demographic information was available for each patient. HRQOL was evaluated with two epilepsy‐specific instruments, the Impact of Pediatric Epilepsy Scale (IPES) and the Epilepsy & Learning Disabilities Quality of Life Questionnaire (ELDQOL); a generic HRQOL instrument, the Pediatric Quality of Life Inventory (PedsQL); and a behavioral screening tool, the Strength and Difficulties Questionnaire (SDQ). Results: Twenty‐eight patients were 10–15 years of age (0–5 years at baseline) and 40 were ≥16 years of age (≥6 years at baseline). Patients 0‐ to 5–years‐old at baseline showed a significant decline in mean scores on the PedsQL total score ( p  = .004), physical score ( p  < .001), cognitive score ( p  = .011), social score ( p  = .003), and eating score ( p  = .030) at follow‐up. On multivariate regression, lower baseline and follow‐up HRQOL for the whole cohort were associated with worse epilepsy severity and a high SDQ total score ( R 2  = 33% and 18%, respectively). In the younger patient group, younger age at first seizure and increased severity of epilepsy were associated with a lower baseline HRQOL ( R 2  = 35%). In the older age group, worse epilepsy severity ( F  = 6.40, p  = .016, R 2  = 14%) and the use of sodium‐channel blockers were independently associated with a lower HRQOL at 10‐year follow‐up ( F  = 4.13, p  = .05, R 2  = 8%). Significance: This 10‐year, prospective follow‐up study highlights the significant HRQOL‐associated cognitive, social, and physical decline particularly affecting younger patients with DS. Sodium channel blocker use appears to negatively impact long‐term HRQOL, highlighting the importance of early diagnosis and disease‐specific management in DS.